AB0397 LUPUS FATIGUE PROBLEMS IN THE RUSSIAN COHORT OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (RENAISSANCE). (2nd June 2020) - Aseeva, E.; Solovyev, S.; Koilubaeva, G.; Nikishina, N.; Nasonov, E.; Lila, A.
Abstract : Background: Objectives: To determine the dependency of fatigue from SLE activity, irreversible organ damage and HRQoL in SLE patients of the Renaissance cohort. Methods: 328 Russian SLE patients were enrolled in the study (M/F 30/298) who fulfilled SLICC 2012 criteria. The SLEDAI 2K activity, SLICC damage index, Facit Fatigue scale, and health related quality of life (HRQol) using the LupusQol questionnaire were evaluated. Results: Based on the Facit Fatigue scale scores fatigue was verified in 148 (45%) out of 328 patients with SLE. Following lupus fatigue status patients were divided into two groups - 148 and 168 patients respectively. The groups were perfectly matched in terms of age, duration of the disease, duration of GCs therapy, and damage scores (Table 1 ) The SLEDAI 2K activity scores were significantly higher in the group with lupus fatigue - 9.6±6.0 vs 6.7±4.2 ( p =0.01) as compared to values in the group without fatigue, as well as the level of antibodies to DNA ( p =0.02), 110.2±34.2 and 82.3±20.5, respectively. There was a significant decrease in HRQoL in patients with lupus fatigue based on scores in all eight scales of the questionnaire ( p =0.00), Conclusion: Almost half (45%) SLE patients in the Russian cohort experience fatigue. It is associated with disease activity on the SLEDAI 2k scale and high levels of antibodies to DNA. All patients experiencing lupus fatigue have significantly worse HRQoL based on scores in all eight scales of the questionnaire LupusQol. Disclosure of Interests: None declared